DIAPHRAGM BREATHING EXERCISE DAN CIRCUIT TRAINING EXERCISE BERPENGARUH TERHADAP CARDIORESPIRATORY FITNESS PEROKOK KONVENSIONAL: DIAPHRAGM BREATHING EXERCISE DAN CIRCUIT TRAINING EXERCISE BERPENGARUH TERHADAP CARDIORESPIRATORY FITNESS PEROKOK KONVENSIONAL - Manuputty, Irene Jeane Maryorin; Pradita, Angria; Fau, Yohanes Deo; Hargiani, Fransiska Xaveria (Indonesian Journal of Physiotherapy, 2025)
Background: The cardiorespiratory fitness level in conventional smokers can decrease significantly and affect the cardiorespiratory organ system. Therefore, special training is needed to help improve the cardiorespiratory fitness of conventional smokers. This study aims to determine the effect of diaphragm breathing exercise and circuit training exercise on the cardiorespiratory fitness of conventional smokers. Methods: This study used a quasi-experimental research design with one-group pretest-posttest design on a population of conventional smokers involving a total sampling of 20 respondents aged 20-26 years. The measuring instrument used was the 6 minutes-walking test (6MWT). Respondents were given diaphragm breathing exercise and circuit training exercise twice a week for a period of 6 weeks. Data analysis was performed using the paired sample t-test. Results: The average data results of the distance traveled before exercise were 436.30 ± 45.045 and the distance traveled after exercise was 606.15 ± 99.909. Then the Sig. value was obtained. 0.000 (p <0.005), these results indicate that there is an effect of diaphragm breathing exercise and circuit training exercise on cardiorespiratory fitness of conventional smokers. Conclusion: Diaphragm breathing exercise and circuit training exercise have an effect on increasing cardiorespiratory fitness in conventional smokers. Keywords: Circuit Training Exercise; Conventional Smoker; Diaphragm Breathing Exercise; Cardiorespiratory Fitness